2004
DOI: 10.1007/978-3-540-25940-4_33
|View full text |Cite
|
Sign up to set email alerts
|

Traction Monitoring for Collision Detection with Legged Robots

Abstract: With the introduction of commercially available programmable legged robots, a generic software method for detection of abnormalities in the robots' locomotion is required. Our approach is to gain satisfactory results using a bare minimum amount of hardware feedback; In most cases we are able to detect faults using only the joint angle sensors. Methods for recognising several types of collision as well as a loss of traction are examined. We are particularly interested in applying such techniques to Sony AIBO ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…On a legged robot, Quinlan et al [29] discuss a method for calibrating the odometry based on the robot's vision-based localization. These methods all rely on already calibrated sensor models to make the action models more accurate.…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…On a legged robot, Quinlan et al [29] discuss a method for calibrating the odometry based on the robot's vision-based localization. These methods all rely on already calibrated sensor models to make the action models more accurate.…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…Furthermore, the motion data of a robot, especially of a legged robot can be uncertain. Noisy motion data are usually caused by slippage, traction loss, or collisions [92,51]. This uncertainty in odometry can result in an erroneous speed model of the object to track.…”
Section: Egocentric World Modelingmentioning
confidence: 99%
“…As an example, when a robot perceives a flag in a certain distance and angle and the robot is moving, the distance and angle of the flag to the robot change. The robot's uncertainty about the flag distance and angle increases, due to motion noise or slippage [92]. Fig.…”
Section: Constraint Prediction Stepmentioning
confidence: 99%
“…In their work they used a supervised learning approach, feeding a decision tree with labeled data collected while the robot was marching in place on different types of surfaces. Quinlan et al [10,11] showed that it is possible to learn normal motion of the limbs for distinct walking directions and used this to detect slippage of the legs and collisions of the robot with its environment. The main drawbacks of this method are that it is not generalized for omnidirectional walking and that it is not independent of collision point.…”
Section: Related Workmentioning
confidence: 99%